Advances in intelligent systems and computing II : selected papers from the International Conference on Computer Science and Information Technologies, CSIT 2017, September 5-8 Lviv, Ukraine /: selected papers from the International Conference on Computer Science and Information Technologies, CSIT 2017, September 5-8 Lviv, Ukraine. ([2018]) - Unknown
No abstract available